Simulation-Based Assessment of ECMO Clinical Specialists. Issue 3 (June 2016) - Fehr, James J.; Shepard, Mark; McBride, Mary E.; Mehegan, Mary; Reddy, Kavya; Murray, David J.; Boulet, John R.
Abstract : Objective: The aims of the study were (1) to create multiple scenarios that simulate a range of urgent and emergent extracorporeal membrane oxygenation (ECMO) events and (2) to determine whether these scenarios can provide reliable and valid measures of a specialist's advanced skill in managing ECMO emergencies. Design: Multiscenario simulation-based performance assessment was performed. Setting: The study was conducted in the Saigh Pediatric Simulation Center at St. Louis Children's Hospital. Subjects: ECMO clinical specialists participated in the study. Measurements and Main Results: Twenty-five ECMO specialists completed 8 scenarios presenting acute events in simulated ECMO patients. Participants were evaluated by 2 separate reviewers for completion of key actions and for global performance. The scores were highest for the hemodilution scenario, whereas the air entrainment scenario had the lowest scores. Psychometric analysis demonstrated that ECMO specialists with more than 1 year of experience outperformed the specialists with less than 1 year of experience. Participants endorsed these sessions as important and representative of events that might be encountered in practice. Conclusions: The scenarios could serve as a component of an ECMO education curriculum and be used to assess clinical specialists' readiness to manage ECMO emergencies. Abstract : Supplemental digital content is available in the text.